A Bibliometric Analysis of Government Budget Efficiency and Effectiveness: Trends and Future Directions - Loso Judijanto; Weda Febriyanto; Tera Lesmana (Westscience Press, 2024)
This study conducts a comprehensive bibliometric analysis of the literature on government budget efficiency and effectiveness, spanning publications from 1956 to 2024. Utilizing data exclusively from Google Scholar and employing VOSviewer for visualization, the analysis identifies key trends, influential themes, and research gaps within the field. The centrality of